Distinction of Characteristics Sharia and Fiqh on Islamic Law - Prawitra Thalib (Yuridika, 2018)
Islamic law has a value of adaptability and flexibility, but also as a revelation that comes from God Almighty, Islamic law also are rigid, immortal and cannot be personalised way. The hallmark of the dynamics and flexibility combined with purity that can’t be fickle that is what makes the uniqueness of the Islamic law as revelation that can answer the entire question of the contemporary that appeared at this time. To understand the Islamic law need to instil an understanding between sharia and fiqh. Of which in respect of Islamic law as revelation from God Almighty, then that’s called Sharia, i.e. a set of international rules from God that its nature remains unchanged and immortal, but when looked at Islamic law is dynamic and flexible that it can adapt to the conditions of time and age then that is called fiqh. Which of course is part of the Islamic fiqh and must not be contrary to the Shariah, this article will lead to an understanding of the concept of Sharia and fiqh in General, to find the characteristics of the eternal, timeless until the day of resurrection, as well as dynamic and versatile development of the times.